2020
DOI: 10.1038/s41598-019-57196-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Retinal Nerve Fibre Layer Thickness on Optical Coherence Tomography with a Deep Learning Segmentation-Free Approach

Abstract: This study describes a segmentation-free deep learning (DL) algorithm for measuring retinal nerve fibre layer (RNFL) thickness on spectral-domain optical coherence tomography (SDOCT). The study included 25,285 B-scans from 1,338 eyes of 706 subjects. Training was done to predict RNFL thickness from raw unsegmented scans using conventional RNFL thickness measurements from good quality images as targets, forcing the DL algorithm to learn its own representation of RNFL. The algorithm was tested in three different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 27 publications
0
28
0
1
Order By: Relevance
“…However, with the advent and development of deep learning, segmentation may be avoidable altogether, and an algorithm could be created to automatically extract features from an unsegmented image. This is one of the notable distinctions between radiomics and deep learning (33,34).…”
Section: Image Segmentationmentioning
confidence: 99%
“…However, with the advent and development of deep learning, segmentation may be avoidable altogether, and an algorithm could be created to automatically extract features from an unsegmented image. This is one of the notable distinctions between radiomics and deep learning (33,34).…”
Section: Image Segmentationmentioning
confidence: 99%
“…Mit dem DL-Modell, das von Mariottoni et al. vorgeschlagen wurde, ließ sich die RNFL in OCT-Bildern mit schlechter Aufnahmequalität besser messen, als mit der Software des Herstellers [ 21 ]. Neben der RNFL und BMO-MRW zeigen sich bei Fortschreiten eines Glaukoms jedoch auch Änderungen anderer anatomischer Strukturen, die auf dem OCT-Scan der Papille sichtbar sind.…”
Section: Künstliche Intelligenzunclassified
“…Therefore these models can make use of raw SDOCT images without requiring the input of pre-defined features. Along those lines, Mariottoni et al 65 recently demonstrated that a segmentation-free deep learning algorithm could be trained to predict RNFL thickness when assessing a raw OCT B-scan. The segmentation-free predictions were highly correlated with the conventional RNFL thickness ( r = 0.983, P < 0.001), with mean absolute error of approximately 2 µm in good-quality images.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to RNFL 65 and optic nerve head scans, 66 , 67 deep learning models have also been used to investigate macular scans. 7 , 68 Asaoka et al 7 showed that a deep learning model built from an 8 × 8 macular grid showed superior performance for detecting glaucoma damage compared to macular RNFL thickness or ganglion cell complex measurements.…”
Section: Introductionmentioning
confidence: 99%